Solar PV and BIPV system: Barrier, challenges and policy recommendation in India - Shukla, Akash Kumar; Sudhakar, K.; Baredar, Prashant; R., Mamat (Elsevier Ltd, 2018)
India receives sun's energy over 300 days a year most of the time. About 5000 trillion kWh per year sun's energy is incident over India's land area. Theoretically, a small fraction of total incident solar energy can meet the entire country's power requirements. There are many government schemes to promote solar power generation. The government of India initiated solar PV/BIPV policies to encourage industries and individuals to use solar energy powered systems for electricity generations. This article provides an overview of the solar energy status and application of BIPV system in India. It includes an assessment of the region's solar energy potential and solar PV/BIPV installed capacity. This paper gives a brief description barriers and challenges facing solar BIPV development in India. This study also provides the solar PV/BIPV policies and recommendations with reference to the Indian context.